Factors associated with knowledge, attitudes, and behaviors regarding antiviral medications for COVID-19 among US adults - E. Ivy Oyegun; Muyiwa Ategbole; Cynthia Jorgensen; Allison Fisher; Melissa Briggs Hagen; Lindsay Gutekunst; Eric Roberts; Emilia H. Koumans (PLoS ONE, 2025)
Background Little is known about public perceptions of antivirals for the treatment of mild-to-moderate COVID-19 in the United States (US). Our objective was to explore adult perceptions toward COVID-19 antivirals to improve outreach communications about antivirals for COVID-19. Methods During July 2022, potential respondents ≥18 years were randomly sampled from a national opt-in internet panel, with oversampling of African Americans, Hispanics, and adults ≥65 years. Respondents were asked about sociodemographic factors, and knowledge, attitudes, and perceptions regarding COVID-19 antivirals. Results were weighted to represent the non-institutionalized US adult population. Results Among 1,155 respondents, 51% were female, 21% were 50−64 years, and 19% were ≥65 years. Compared to younger age groups, a greater proportion of adults ≥65 years were knowledgeable about COVID-19 antivirals and would take them if they tested positive or their doctor recommended them. Adults ≥65 years and those reporting immunosuppression or disability had the highest rates of willingness to take antivirals. For all groups, the proportion of people willing to take antivirals increased by >20% if recommended by their doctor. Respondents in the 50−64 and ≥65 groups who were sure they would take COVID-19 antivirals were more likely to be fully vaccinated and less likely to be living in isolation. Conclusion Groups that are less likely to have been vaccinated, those living in isolation, and those not sure about whether they would take an antiviral or not may be at risk for not receiving treatment to prevent severe COVID-19 outcomes. However, trust in doctor recommendations may be enough to overcome individual patient concerns about COVID-19 antivirals. Targeted initiatives to educate those at risk for severe COVID-19 outcomes about the effectiveness of antivirals may be needed to further lower this population’s risk of severe COVID-19.